2015
DOI: 10.18388/abp.2015_1146
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silver nanoparticles on metabolism and toxicity of moulds

Abstract: The unique antimicrobial features of silver nanoparticles (AgNPs) are commonly applied in innumerable products. The lack of published studies on the mechanisms of AgNPs action on fungi resulted in identification of the aim of this study, which was: the determination of the influence of AgNPs on the mould cytotoxicity for swine kidney cells (MTT test) and the production of selected mycotoxins, organic acids, extracellular enzymes by moulds. The conducted study had shown that silver nanoparticles can change the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…The highest activity was obtained for silver-modified nanocomposites obtained by chemical reduction, characterized by small particle size. The improvement of antimicrobial properties of metal-modified titanium(IV) oxide is possible due to the synergism of the antimicrobial properties of metals and reactive oxygen species generation on the TiO 2 surface [3,79,80,81,82,83]. For gram-negative strains, silver nanoparticles are able to absorb and accumulate on the outer cell wall leading to the disintegration of the lipid bilayer and an increase in its permeability.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The highest activity was obtained for silver-modified nanocomposites obtained by chemical reduction, characterized by small particle size. The improvement of antimicrobial properties of metal-modified titanium(IV) oxide is possible due to the synergism of the antimicrobial properties of metals and reactive oxygen species generation on the TiO 2 surface [3,79,80,81,82,83]. For gram-negative strains, silver nanoparticles are able to absorb and accumulate on the outer cell wall leading to the disintegration of the lipid bilayer and an increase in its permeability.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The findings indicate that Ag NPs inhibit fungal growth as well as morphological and metabolic changes [ 85 , 86 ]. For instance, the application of 45 ppm Ag NPs caused a decrease of organic acid (oxalic, maleic, and citric acid) production, mycotoxin production (up to 80%), and changes in the enzymatic profile in Aspergillus niger and Penicillium chrysogenum [ 85 ]. All the studies reviewed so far, however, suffer from the fact that the interaction of NPs with the individual components of the fungi cells has not been investigated yet.…”
Section: Nano Approaches For Mycotoxin Risk Eliminationmentioning
confidence: 99%
“…The nanosized silver can inhibit the growth of Fusaium sp. at very low concentrations (<100 ppm) [ 16 , 60 ] and led to decreased mycotoxin production [ 1 , 61 ]. Also, Kischkel et al [ 37 ] observed the antifungal activity of the AgNPs against C. albicans , F. oxysporum and M. canis .…”
Section: Applications Of Nanoantifungals In Veterinary Medicinementioning
confidence: 99%